Treatment patterns and healthcare resource utilization in patients with FLT3‐mutated and wild‐type acute myeloid leukemia: A medical chart study. (5th February 2019) - Griffin, James D.; Yang, Hongbo; Song, Yan; Kinrich, David; Shah, Manasee V.; Bui, Cat N.
Abstract: Objectives: To assess real‐world treatment patterns and healthcare resource utilization (HRU) among patients with FLT3 –mutated ( FLT3 mut ) and FLT3 –wild‐type ( FLT3 wt ) acute myeloid leukemia (AML). Methods: Data were abstracted from medical charts of patients with AML from 10 countries. Patients were grouped based on their FLT3 mutation status, age (18‐64 or ≥65), and whether they were newly diagnosed (ND) or relapsed/refractory (R/R). Results: Charts of 1027 AML patients were included (183 FLT3 mut 18‐64 ND; 136 FLT3 mut ≥65 ND; 181 FLT3 mut R/R; 186 FLT3 wt 18‐64 ND; 159 FLT3 wt ≥65 ND; 182 FLT3 wt R/R). Substantial heterogeneity was observed in treatment patterns for AML. Among ND patients 18‐64, the most common initial treatment was standard‐to‐intermediate dose cytarabine‐based therapies (43.2% for FLT3 mut and 55.9% for FLT3 wt ); among ND patients ≥65, the most common initial treatment was hypomethylating agent‐based therapies (36.0% and 47.2%). Among R/R patients, the most common initial treatment after R/R was best supportive care only (39.8% and 24.7%). HRU was substantial across cohorts during both event‐free and post‐event periods. Conclusions: Treatment patterns of AML were heterogeneous and FLT3 mut AML was treated more aggressively than FLT3 wt disease. HRU was substantial for all cohorts, particularly after relapse or treatment failure.